Understanding Reintensified Multiyear El Niño Events. Issue 12 (24th June 2020) - Kim, Ji‐Won; Yu, Jin‐Yi
Abstract: To understand the unique temporal evolution of the 2014–2016 multiyear El Niño event, which can be characterized as a successive and reintensified event preceded by a weak El Niño, this study examines similar events in a 2, 200‐yr simulation of Community Earth System Model, version 1. By contrasting multiyear El Niño events with single‐year ones, we find that the succession characteristics of multiyear El Niño events are primarily caused by a negative North Pacific Oscillation (NPO) in the first‐year winter via subtropical Pacific coupling processes. By contrasting reintensified multiyear El Niño events with lingering ones, we find that the reintensification characteristics are caused by a negative Indian Ocean Dipole (IOD) in the first‐year fall via tropical interbasin coupling processes. The phase information of the preceding winter NPO and fall IOD together can be used to project the evolution characteristics of El Niño events, particularly the reintensified multiyear and transitional single‐year events. Plain Language Summary: The 2015–2016 El Niño, categorized as a very strong event like the 1997–1998 and 1982–1983 events, was unique in its evolution in time as it was preceded by a weak El Niño. By analyzing a long‐term simulation produced by a state‐of‐the‐art climate model, this study uncovers two key factors driving these types of multiyear El Niño events: a meridional shift of the northern winter Aleutian Low pressure system over the North Pacific (known as the North Pacific Oscillation) and a zonal dipole‐like pattern of northern fall sea surface temperatures in the Indian Ocean (known as the Indian Ocean Dipole). This study also explains how these two factors invoke tropical‐extratropical interactions in the Pacific and interbasin interactions between the Indian and Pacific Oceans to give rise to the evolution characteristics of these multiyear events. Findings from this study may help improve predictions of multiyear El Niño events. Key Points: The CESM1 model frequently simulates a type of reintensified multiyear El Niño events resembling the 2014–2016 extreme El Niño The succession and reintensification characteristics of these events are associated with negative phases of the NPO and IOD, respectively The phases of NPO and IOD are closely related to the occurrences of reintensified multiyear and transitional single‐year El Niño events